Investigating the molecular mechanism of sterility in female triploid Pacific oyster (Crassostrea gigas) - Enshuo Zhang; Zan Li; Bin Li; Jingjing Fu; Yanwei Feng; Guohua Sun; Xiaohui Xu; Cuiju Cui; Weijun Wang; Jianmin Yang (Aquaculture Reports, 2024)
The emergence of triploid oysters has freed the oyster market from the problem of interruptions in the breeding season, allowing for year-round availability. However, according to recent statistics, the phenomenon of fertility in triploid oysters has been increasing yearly, perhaps eventually leading to the loss of the sterility characteristic. This has in turn affected the oyster farming industry. Therefore, we attempted to mine key genes through transcriptomics to find the causes of triploid fertility. During our surveys and sampling, we found that most of the fertile triploid Crassostrea gigas were females, with a much smaller percentage of males. Therefore, the main objective of this study was to analyze the differences between fertile and sterile triploid female C. gigas. We performed transcriptome analysis of fertile female triploid C. gigas and sterile female triploid C. gigas and identified 2361 up-regulated differentially expressed genes (DEGs) and 1541 down-regulated DEGs, respectively. Enrichment analysis of these DEGs revealed that most GO terms and KEGG pathways were associated with mitosis. We then created a protein–protein interaction (PPI) network using genes enriched in mitosis-associated KEGG pathways. Finally, we screened and validated 26 key genes by quantitative RT-PCR and all were found to be downregulated in expression in sterile female triploids. The main cause of sterility is the suppression of the expression of genes that control the process of germ cell proliferation, the failure of the mitotic cycle to proceed smoothly, and the inability to produce an oogonium. These results can be used to explore ways to reduce the fertility of triploid C. gigas and to promote the breeding of higher quality triploid oysters.